Ballistic impact performance of UHMWP fabric impregnated with shear thickening fluid nanocomposite. (1st February 2022) - Mishra, Vagish D.; Mishra, Ashish; Singh, Avinash; Verma, Luv; Rajesh, G.
Abstract: In the present study, an attempt is made to improve the ballistic performance of unidirectional (UD) ultra-high molecular weight polyethylene (UHMWP) fabrics through shear thickening fluid (STF) impregnation. Impact tests in the range of 250–700 m/s were conducted using an aero-ballistic range. It was observed that the ballistic limit (V50 ) and the energy absorption of STF treated UD-UHMWP fabrics can be improved up to 5% and 13% respectively, corresponding to their neat ones. Increased energy absorption of STF treated fabric is attributed to the enhancement in the friction between layers of the STF-UHMWP fabric and the shear thickening effect. The effect of sample thickness of STF treated panels on the energy absorption, failure mechanism, and back face signature (BFS) is evaluated and compared with their neat counterparts. The damage was localized in the thinner panels (5 and 10 layers), and the layers were perforated through shear plugging near the impact region. The failure mode of thicker panels (20 and 30 layers) is accompanied by the tensile fracture of high tenacity fibres. It is concluded that the STF impregnation improves the ballistic resistance of UD-UHMWP fabric without affecting the flexibility and adding weight penalty.